Adsorption of fluoride from aqueous solution by alumina of alkoxide nature: batch and continuous operation - Kamble, Sanjay P.; Deshpande, Gunavant; Barve, Prashant P.; Rayalu, Sadhana; Labhsetwar, Nitin K.; Malyshew, Alexander; Kulkarni, Bhaskar D. (Desalination, 2010)
In this investigation, we report the adsorption potential of alkoxide origin alumina for defluoridation of drinking water using batch and continuous mode of operations. The effects of different operating parameters such as adsorbent dose, initial fluoride concentration, pH of the solution and interfering ions (usually present in groundwater) were studied with a view to understand the adsorption behavior of the material under various conditions. A thermodynamic study shows that the adsorption of fluoride by alkoxide origin alumina is an exothermic and spontaneous process. The kinetic results showed that the fluoride sorption follows pseudo-second-order kinetics. The applicability of adsorbent in the field is also tested through column breakthrough studies. It has been observed that with an increase in the flow rate and initial fluoride concentration, the breakthrough curve becomes sharper and the breakthrough time and adsorbed fluoride ion concentration decrease. The breakthrough curve also becomes steeper as the bed height increases. The alkoxide origin alumina based adsorbent media can be used directly for field applications since it is also commercially available in granular form. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Alkoxide alumina; Breakthrough studies; Fluoride; Kinetic modeling

Alumina supported carbon composite material with exceptionally high defluoridation property from eggshell waste - Lunge, Sneha; Thakre, Dilip; Kamble, Sanjay; Labhsetwar, Nitin K.; Rayalu, Sadhana (Journal of Hazardous Materials, 2012)
A new alumina supported carbon composite material called ``Eggshell Composite'' (EC) was synthesized from eggshell waste as calcium source for selective fluoride adsorption from water. The effect of various synthesis parameters like eggshell (ES): Eggshell membrane (ESM) ratio, aluminium loading, mixing time and calcinations temperature to optimize the synthesis conditions for selective fluoride removal has been studied. It was observed that the synthesis parameters have significant influence on development of EC and in turn on fluoride removal capacity. EC synthesized was characterized for elemental composition, morphology, functionality and textural properties. Results showed that EC obtained from eggshell modified with alumina precursor is more selective and efficient for fluoride removal. Langmuir and Freundlich isotherm were used to obtain ultimate fluoride removal capacity. The calcium and alumina species in EC shows synergistic effect in fluoride adsorption process. Fluoride sorption studies were carried out in synthetic, groundwater and wastewater. EC proved to be a potential, indigenous and economic adsorbent for fluoride removal. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Composite material; Eggshell; Eggshell membrane; Fluoride adsorption; Langmuir

Orthorhombic/cubic Cd2SnO4 nanojunctions: enhancing solar water splitting efficiency by the suppression of charge recombination - Deshpande, Aparna; Kelkar, Sarika A.; Rayalu, Sadhana; Ogale, Satishchandra (Journal of Materials Chemistry A, 2014)
The low practical efficiency of binary metal oxide semiconductor-based photo-electrochemical (PEC) water splitting has prompted researchers to examine ternary and quaternary oxides, which provide more leverage for engineering the desired PEC properties via stoichiometry (valence) and phase control. One ternary system of interest in this context is cadmium tin oxide (Cd2SnO4), which supports the cubic and orthorhombic phases with optical, electronic and catalytic properties that are favourable for PEC water splitting. However, its practical PEC performance is limited by high surface recombination of the photogenerated charge carriers. In this work we circumvent this problem by engineering the constitution of Cd2SnO4 nanoparticles to a biphasic nanojunction form, comprising of a nanocomposite of cubic and orthorhombic phases. The favourable conduction band alignment between the cubic and orthorhombic phases leads to a dramatic reduction in the recombination of the photogenerated charges, leading to a 10-fold increase (from 250 mu A cm(2) to over 2 mA cm(2)) in the photocurrent vis-a-vis the single cubic or orthorhombic phase performance. We discuss the underlying mechanism for the observed dramatic enhancement in the water splitting efficiency.